Biocompatibility and biodegradation analysis of Nile Tilapia gelatin and apatite membranes - Maria de Sousa, Efigênia (Revista Ciência Agronômica, 2021)
Fish farming by-products could represent large-scale raw materials for xenogeneic implants that could be used forbone regeneration. The objective of this research was to analyze the biocompatibility and biodegradation of gelatin (G) and apatite (A)membranes from Nile tilapia. Adult male Swiss mice underwent subcutaneous implantation of biocomposites derived from skins andscales in different concentrations: 60%G:40%A (G1), 70%G:30%A (G2) and 80%G:20%A (G3). Commercial collagen membrane (C+) orimplantless surgery (C–) were used as controls. Euthanasia was performed at 1, 3 or 9 weeks for histological analysis of the infl ammatoryand repair criteria as well as the integrity of each material. The statistical analysis of non-parametric data was performed using the KruskalWallis test and post-hoc Dunn test, with p < 0.05. In vivo results during the experimental period demonstrated progressive improvement inbiocompatibility, with G1 and G2 being slightly irritating and G3 non-irritating, just like C+. There were signifi cant differences betweentest and control groups regarding the presence of neutrophils, lymphocytes, macrophages, foreign body giant cells, neovascularizationand connective tissue. There was also a decrease in the integrity of the implants, where G1 maintained greater stability than G3 and G2,but less than C+. All biocomposites proved to be biocompatible and partially biodegradable. G1 suggests greater potential for use as anosteopromoting membrane, with its biological performance associated with higher mineral concentration compared to the organic phase.Future long-term orthotopic studies will be conducted to investigate its osteopromoting action.